1993
DOI: 10.1093/nar/21.22.5235
|View full text |Cite
|
Sign up to set email alerts
|

Functional redundancy of octamer elements in the mouse mammary tumor virus promoter

Abstract: The promoter of mouse mammary tumor virus contains three overlapping sequence elements related to the octamer consensus (ATGCAAAT) that are largely contained within two 10 bp direct repeats (CTTATGTAAA) separated by a 2 bp spacer between 60 and 39 relative to the start of transcription. Gel electrophoresis mobility shift competition assays demonstrate that the most distal of these octamer-related elements is recognized by a protein that also binds to the most proximal element, while the central octamer-related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Alternatively, the two regulatory sites may act at different stages of development, since Cdc14 transcripts persist from early sporulation until cyst germination (1). Genes regulated by multiple inputs via distinct promoter modules are common in prokaryotes and eukaryotes, as are promoters containing functionally redundant transcription factor sites (16,18,25).…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the two regulatory sites may act at different stages of development, since Cdc14 transcripts persist from early sporulation until cyst germination (1). Genes regulated by multiple inputs via distinct promoter modules are common in prokaryotes and eukaryotes, as are promoters containing functionally redundant transcription factor sites (16,18,25).…”
Section: Discussionmentioning
confidence: 99%
“…Ample evidence suggests that the MMTV LTR is occupied by an array of six nucleosomes (16,70) that have compositions typical of eukaryotic chromatin (two each of histones H2A, H2B, H3, and H4) (72). Chromatin structure has been shown to change in the presence of glucocorticoids (69,70,86,98), and it is believed that this change allows promoter activation through the binding of transcriptional activators such as NF-1 and Oct-1 and the basal transcription apparatus (20,48). In agreement with this idea is the recent observation that the RNA polymerase II holoenzyme contains SWI/SNF, a protein complex that can disrupt nucleosomes (94).…”
mentioning
confidence: 99%
“…The MMTV promoter contains three overlapping octamer-related sequences between the TATA box and a binding site for NF-1. We (26,58), as well as others (5), have reported specific binding to these sequences by proteins present in nuclear extracts of various cultured cell lines, and our results strongly suggested that only the nonoverlapping octamer-related elements most proximal and most distal to the transcription start site are efficiently recognized (26). In addition, Brüggemeier et al (5) have reported that partially purified Oct-1 binds to the MMTV octamer-related sequences; however, the Oct-1 preparation used in these studies was not extensively described.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously demonstrated that octamer-related sequences are important for both basal and steroid hormone-induced MMTV promoter activity in a transient-transfection assay in mouse Ltk Ϫ cells (26,58). To begin to determine the molecular details of the role of octamer-related sequences in MMTV promoter activity, we turned to in vitro transcription assays.…”
Section: Mutations In Octamer-related Sequences Decrease Mmtv Promotementioning
confidence: 99%
See 1 more Smart Citation